Maximum Principles for Dynamic Equations on Time Scales and Their Applications - Shuqing Zhou; Hui Li (Journal of Applied Mathematics)
We consider the second dynamic operators of elliptic type on time scales. We establish basic generalized maximum principles and apply them to obtain weak comparison principle for second dynamic elliptic operators and to obtain the uniqueness of Dirichlet boundary value problems for dynamic elliptic equations.